(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Habitat fragmentation is a critical environmental issue with significant implications for biodiversity, particularly in tropical ecosystems, which are known for their rich species diversity. Fragmentation occurs when large, continuous habitats are broken into smaller, isolated patches, often due to human activities such as deforestation, urbanization, and agriculture. In tropical ecosystems, this disruption leads to a loss of species, as smaller patches of habitat support fewer individuals and reduced genetic diversity. The effects of habitat fragmentation are particularly severe in tropical environments because these areas host a large number of endemic species—species that are found nowhere else on Earth. Fragmentation reduces the available space for species to thrive, leading to increased competition for resources, isolation of populations, and a higher risk of local extinctions. Additionally, fragmented habitats often face edge effects, where the environmental conditions at the boundary of the habitat differ from those in the interior, further threatening sensitive species. The loss of biodiversity in tropical ecosystems due to habitat fragmentation have cascading effects, disrupting ecological processes and services such as pollination, seed dispersal, and nutrient cycling. Addressing this issue is essential for preserving global biodiversity and ecosystem resilience.